Synthesis of coral-like, straw-tied-like, and flower-like antimony sulfides by a facile wet-chemical method - Kavinchan J. (2014)
Antimony sulfide (Sb2S3) was successfully synthesized from antimony chloride (SbCl3) and sodium thiosulfate pentahydrate (Na2S2O3·5H2O) in ethylene glycol (EG) without using any template by a facile wet-chemical method. X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) show that the products were orthorhombic Sb2S 3 nanorods forming the coral-like, straw-tied-like, and flower-like architectures with the nanorods growing along the [001] direction. The energy gap (E g) was determined by UV-visible absorption to be 1.52 eV. © 2013 Jutarat Kavinchan et al.